Navigating the Terrain of Lived Experience: The Value of Lifeworld Existentials for Reflective Analysis - Stephanie Rich BApSc (Health Promotion) (Hons) (International Journal of Qualitative Methods, 2013)
In qualitative research we are often presented with a tension between having open and fluid interviews to support staying true to the lived experiences of participants and achieving a level of abstraction from the data in order to uncover the essential structures and meanings of that particular lived experience. A way of resolving this tension is through the application of theoretical frameworks. Van Manen's four lifeworld existentials offer a lens through which to explore and navigate disparate interview data and uncover the essences of lived experience, without imposing categories upon the data itself. Drawing on a study exploring the lived experiences of childless women, we explore the process and principles in operationalising the existentials and discuss the potential implications for analysis and findings. The article demonstrates how Van Manen's lifeworld existentials present us with a holistic and valuable method for reflective practice, in coming to understand lived experience.